COMMUNICATION POLITENESS STRATEGY OF MAHFUDZ M.D IN ANSWERING ABOUT THE LAW ON ‘NARASI’ - Dwi Santoso; Rahma Amini Isnaini (Ikatan Dosen Menulis, 2023)
Communication using the politeness strategy is something that is very attached to everyone. Each person will have a different form of politeness. Researcher use qualitative methods a) transcript of the video content of Mahfud MD in the Narasi show from minute 20 to 50 with a total duration of 30 minutes b) Identifying the type of communication politeness strategy in Mahfud MD's answers in the Narasi show. The findings found that Mahfudz MD uses three of the five types of politeness strategies, namely bald on record, positive, negative, and off-record politeness, and most often uses positive politeness for communication on Narasi with the theme law as moral demand in Indonesia.